Development of Augmented Reality Learning Media Based on Culturally Responsive Teaching (CRT) to Improve Learning Outcomes in Science Material - Naviatul Rizqia; Moh. Fathurrahman; Zahidah Mahroini (Indonesia Approach Education, 2024)
This research was motivated by the application of technology-based learning media. Based on the results of a preliminary survey conducted in grade IV 1 Elementary School Soditan, Rembang Regency, problems were identified with limited learning media and low student learning outcomes in science content. Therefore, learning media is needed as an alternative solution to social studies learning problems in grade IV SD Negeri 1 Soditan even semester. The purpose of this study is to develop an augmented reality learning media design based on culturally responsive teaching, test its feasibility, and test its effectiveness. The type of research used is Research and Devolopment (R&D) with the Borg and Gall development model. Data collection techniques use test techniques and non-test techniques consisting of observation, interviews, questionnaires, and documentation. Product suitability is assessed by material experts and media experts with a percentage of 93.75% and 90% with a classification of